The Effect of Workload on Concentration Disorders With Work Stress in PT Oragon Technology Indonesia - Nawawi, Yusuf; M Zainul, L.; Rusba , Komeyni; Khatami Fahmi Putra, Muhammad; Zulfikar, Iwan (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study examines the impact of workload on concentration disorders, with work stress as a mediating variable at PT Oragon Teknologi Indonesia. High workload is linked to increased work stress, which can impair concentration. The research uses a qualitative approach, collecting data through in-depth interviews, participatory observation, and document analysis. Results show a significant relationship between high workload and increased work stress, which directly affects employee concentration. Interviews with 20 employees reveal that time pressure, excessive tasks, and lack of support from superiors are key factors increasing workload and stress. The study suggests that PT Oragon Teknologi Indonesia should implement effective workload management strategies, such as task balancing, enhanced support from superiors, and stress management programs, to reduce concentration disorders. These findings contribute to human resource management literature and industry practices in managing employee workload and stress.